A comparative study of bare and seawater sea sand concrete wrapped basalt fiber-reinforced polymer bars exposed to laboratory and real marine environments. (31st March 2023) - Feng, Guangyan; Zhu, Deju; Guo, Shuaicheng; Rahman, Md Zillur; Ma, Wenbo; Yi, Yong; Jin, Zuquan; Shi, Caijun
Highlights: Low-alkalinity seawater sea sand concrete was applied to improve the durability of FRP bars in marine concrete structures. The durability of BFRP bars embedded in SWSSC in the laboratory and real marine environments under various exposure periods were compared. The deterioration mechanism and microstructures of BFRP bars embedded in ordinary and low alkalinity SWSSCs were investigated using 1H NMR, FTIR, TG and SEM. Abstract: The high alkalinity of concrete restricts the application of basalt fiber-reinforced polymer (BFRP) bars as reinforcement in seawater and sea sand concrete (SWSSC), but lowering the alkalinity enhances the durability of BFRP bars. This work focuses on the degradation of BFRP bars embedded in SWSSC in the laboratory and real marine environments. The interlaminar shear strength (ILSS) and deterioration mechanisms of BFRP bars wrapped in ordinary and low-alkalinity SWSSCs were investigated using the ILSS test, 1 H nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). It was found that the BFRP bars in the natural marine environment suffer from less degradation than those in the accelerated laboratory environment due to the lower temperature. After 180 d of exposure to 55 °C seawater and the field environment, the ILSS retentions of BFRP bars in ordinary SWSSC are 54% and 85%, while those in low-alkalinity SWSSC remain 81% and 97%, respectively. The decreased alkalinity and porosity in low-alkalinity SWSSC also considerably minimize the hydrolysis of epoxy resin in BFRP bars caused by alkaline and moisture erosion. Furthermore, the Arrhenius theory-based model considering temperature and humidity fluctuations, predicts that lowering the alkalinity of SWSSC can greatly enhance the service life of BFRP bars, which can be applied in high-temperature and humidity environments. This study provides insights into using low-alkalinity SWSSC to improve the durability of FRP bars in marine concrete structures.